Cognitive Distortion Scale for Bangladesh: Development and Properties (Dhaka University Journal of Biological Sciences, 2024)
The purpose of the study was to develop a scale for assessing cognitive distortions in Bangladesh and establishing psychometric properties for Bangladeshi population. The scale was named as Bangladesh Cognitive Distortion Scale (BCDS). Items were constructed through three stages of intensive expert evaluation where 128 respondents participated and both item analysis and factor analysis were undertaken. Finalized BCDS with 39 items was administered to 478 respondents to calculate its psychometric properties. Concurrent validity of BCDS was found 0.828 by calculating correlation between the score of BCDS and clinician’s subjective rating. Predictive validity considering anxiety and depression scale was found 0.756 and 0.841, respectively. Convergent validity (0.670) was confirmed through the correlation between the DAS and BCDS and divergent validity was established by the discriminate value (F=649.564, α